The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/d0ew00205d
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic reductive defluorination of perfluorooctanoic acid in water under visible light irradiation: the role of electron donor

Abstract: Visible light-driven defluorination of PFOA was achieved via a photo-reductive pathway by using Pt–Bi2O4 as a photocatalyst and KI as an electron donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The legendary photocatalyst, pristine-/modified-titanium dioxide (TiO 2 ), , and the photocorrosion resistant pristine-/modified-bismuth oxyhalide (BiOX) photocatalysts ,,,, equally share this investigation (5 publications each). The photocatalytic degradation of PFOA has been explored (4 publications) over photostable, modified indium oxide (In 2 O 3 ) photocatalysts. ,, Only a single article each on modified zinc oxide (ZnO) and bismuth oxide photocatalysts is reported. The remainder of the articles explored the photocatalytic degradation of PFA over binary composite materials combining BiOX , and ZnO, cerium oxides (CeO 2 ) and layered double hydroxides, iron oxides (FeO), and carbon spheres …”
Section: Present Status Of Photocatalytic Degradation Of Pfamentioning
confidence: 99%
See 1 more Smart Citation
“…The legendary photocatalyst, pristine-/modified-titanium dioxide (TiO 2 ), , and the photocorrosion resistant pristine-/modified-bismuth oxyhalide (BiOX) photocatalysts ,,,, equally share this investigation (5 publications each). The photocatalytic degradation of PFOA has been explored (4 publications) over photostable, modified indium oxide (In 2 O 3 ) photocatalysts. ,, Only a single article each on modified zinc oxide (ZnO) and bismuth oxide photocatalysts is reported. The remainder of the articles explored the photocatalytic degradation of PFA over binary composite materials combining BiOX , and ZnO, cerium oxides (CeO 2 ) and layered double hydroxides, iron oxides (FeO), and carbon spheres …”
Section: Present Status Of Photocatalytic Degradation Of Pfamentioning
confidence: 99%
“…Confirmatory molecular dynamic density functional theory simulations will then provide the necessary theoretical framework. Several articles have claimed that • OH is not part of any photocatalyzed destruction of PFOA. ,,, On the contrary, several other articles have been published discussing the photocatalytic degradation of PFOA by • OH radicals through the following proposed reactions. The h VB + and • OH radicals can both oxidize PFO – to generate C 7 F 15 COO • radicals, which can undergo the Kolbe decarboxylation reaction to produce an unstable alkyl radical ( • C 7 F 15 ) and CO 2 (Reaction -).…”
Section: Present Status Of Photocatalytic Degradation Of Pfamentioning
confidence: 99%
“…To overcome the slow decomposition kinetics of organic compounds, photoactive catalysts (e.g., TiO 2 , titanate nanotubes [TNTs], Fe/TNTs@AC, and boron nitride) have been tested to accelerate PFAS degradation using ultraviolet C (UVC, wavelength 200–280 nm) irradiation ( Chen et al, 2011 ; Duan et al, 2020 ; Li et al, 2020 ; Sansotera et al, 2014 ; Wang & Zhang, 2011 ). Recently, photocatalysts that worked under visible light (VL, wavelength over 400 nm) were used in a proof-of-concept study carried out with model solutions ( Wang, Cao, et al, 2020 ; Wang, Chen, et al, 2020 ; Xu et al, 2020 ). The hydrophobicity of photocatalyst surfaces holds promise to enhance PFAS interaction with the catalyst and was a reason for explaining superior (i.e., lower energy requirements) defluorination of PFOA on boron nitride than TiO 2 photocatalysts with UV light ( Duan et al, 2020 ).…”
Section: Defluorination Of Pfas In Concentratesmentioning
confidence: 99%
“…6 Because of their resistance to conventional chemical treatments, immense interest has recently focused on photo-induced processes for directly decomposing PFAS contaminants. [7][8][9][10][11] In contrast to conventional filtration techniques that merely remove PFAS (which still require subsequent treatment after filtration), very recent studies have suggested that PFAS degradation can be accelerated with electromagnetic/optical fields, such as those used in photocatalysis or commercially available laser sources. [7][8][9][10][11][12] While these recent findings hold immense promise for directly treating PFAS, the exact mechanisms in these degradation processes remain unknown, 8 and a guided path for rationally identifying photoactive materials and experimental conditions remains elusive.…”
Section: Introductionmentioning
confidence: 99%